2019
DOI: 10.1021/acs.nanolett.9b02520
|View full text |Cite
|
Sign up to set email alerts
|

Giant Fine Structure Splitting of the Bright Exciton in a Bulk MAPbBr3 Single Crystal

Abstract: Exciton fine structure splitting in semiconductors reflects the underlying symmetry of the crystal and quantum confinement. Since the latter factor strongly enhances the exchange interaction, most work has focused on nanostructures. Here, we report on the first observation of the bright exciton fine structure splitting in a bulk semiconductor crystal, where the impact of quantum confinement can be specifically excluded, giving access to the intrinsic properties of the material. Detailed investigation of the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 76 publications
3
73
2
Order By: Relevance
“…3 or more absorption peaks observed in case of PEA 2 PbI 4 . 34,58 In addition, states which are split due to the exchange interaction behave in a characteristic way in magnetic field 74,76,78 shifting in opposite directions, leading to an increased splitting in magnetic field which is not the case here. At the same time the energy of the organic spacer vibrations is expected to only weakly depend on the thickness of the inorganic part.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…3 or more absorption peaks observed in case of PEA 2 PbI 4 . 34,58 In addition, states which are split due to the exchange interaction behave in a characteristic way in magnetic field 74,76,78 shifting in opposite directions, leading to an increased splitting in magnetic field which is not the case here. At the same time the energy of the organic spacer vibrations is expected to only weakly depend on the thickness of the inorganic part.…”
mentioning
confidence: 68%
“…Similarly to the case of 3D perovskites, the edges of the conduction and valance bands are predominantly built from lead orbitals with total angular momentum of 1/2. The qualitative impact of spin-orbit interaction, Coulomb and exchange interaction on excitons state is well known and has already been presented and discussed in literature for 3D [74][75][76] and 2D perovskites. 77 In short, there are only two exciton states that couple effectively to light propagating in the direction perpendicular to the quantum well surface, which can therefore be observed in the absorption spectrum.…”
mentioning
confidence: 99%
“…Alternative techniques like ultrafast photoluminescence would probe the exciton properties immediately after its annihilation, which is suitable neither to accurately track exciton ionization in semiconductors nor to identify the spectral signatures of Mahan excitons 56,57 (in particular the above-gap absorption enhancement). Third, the combination of large excitation densities above n M and RT: While lowering the temperature leads to a sharper quasi-Fermi surface, it also induces structural phase transitions 58 , fine-structure splittings 59 , and polaronic sidebands 60 that render the isolation of the spectroscopic fingerprint due to Mahan excitons very challenging. The final reason lies in the choice of the present material.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] In these studies, however, the reported values of g ⊥ suggest a nontrivial dependence on the environment, and the exciton binding energy of MAPbBr 3 single crystals in the low-field limit was found to differ substantially from that of MAPbBr 3 thin films in the high-field limit, an effect attributed to polarons. 21,23 Additionally, a study on cryogenic MCD of tri-iodide films also suggested a field-dependent exciton binding energy. 20 These examples indicate that perovskites might not follow expected trends.…”
Section: Introductionmentioning
confidence: 86%
“…The third (diamagnetic) term can be neglected at such low magnetic field strengths. 21 The data point for MAPbBr 3 at 0.46 T is directly behind that of MAPbCl 3…”
Section: T a B L E 1 Magneto-optic Properties Of Perovskitesmentioning
confidence: 92%